If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) + 12x = 4 + -7(2 + -1x) Reorder the terms: 5(3 + x) + 12x = 4 + -7(2 + -1x) (3 * 5 + x * 5) + 12x = 4 + -7(2 + -1x) (15 + 5x) + 12x = 4 + -7(2 + -1x) Combine like terms: 5x + 12x = 17x 15 + 17x = 4 + -7(2 + -1x) 15 + 17x = 4 + (2 * -7 + -1x * -7) 15 + 17x = 4 + (-14 + 7x) Combine like terms: 4 + -14 = -10 15 + 17x = -10 + 7x Solving 15 + 17x = -10 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 15 + 17x + -7x = -10 + 7x + -7x Combine like terms: 17x + -7x = 10x 15 + 10x = -10 + 7x + -7x Combine like terms: 7x + -7x = 0 15 + 10x = -10 + 0 15 + 10x = -10 Add '-15' to each side of the equation. 15 + -15 + 10x = -10 + -15 Combine like terms: 15 + -15 = 0 0 + 10x = -10 + -15 10x = -10 + -15 Combine like terms: -10 + -15 = -25 10x = -25 Divide each side by '10'. x = -2.5 Simplifying x = -2.5
| 2(m-5)+6=2m+22 | | x-0.25x=95 | | X^3+28X^2=0 | | x+3-2x=5 | | 2(m-5)+6=2m-1 | | x^2=392 | | -3x-4y(3x+3y)=-1 | | x^2+y^2=784 | | -3x-9=-75+3x | | 2(m-5)+6= | | 1-5x=10-2x | | -6=3(u+-3) | | 15x+6=2x-3 | | 3x+7=6x+7 | | 4(n-3)-2(-3+n)= | | -3(-5u+6)-3u=4(u-6)-8 | | 10+4y= | | 8(4x-1)-12x=(2x-6) | | n(2)+14=98 | | n(2)14=98 | | -1/2x+3(0)=-3 | | 2log(2x)=1 | | -6=3-m | | 125n^2-45=0 | | 0.04x+0.03(x-20)=1.25 | | 6x-61=-3x+65 | | 4(w+1)+4=20 | | 5x-3=6x-7 | | -3e+2=5e-4 | | 3-.75x=8 | | 8b^2+10b+3=0 | | 7x-10=-2-x |